A modern history of Japan : From Tokugawa times to the present - Gordon, Andrew (Oxford University Press, 2019)
This text gives a detailed survey of Japan's history from the Tokugawa shogunate through modern times, exploring political, social, economic, and cultural changes, including modernization, war, occupation, and post-war recovery.